2018
DOI: 10.1111/inr.12455
|View full text |Cite
|
Sign up to set email alerts
|

The impact of simulation education on self‐efficacy towards teaching for nurse educators

Abstract: The Minister of Health in India recently called for improvements in nursing education. Introducing nursing education on simulation as a teaching method in India and globally to improve self-efficacy among teachers is an example of a strategy towards meeting this call.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 19 publications
2
22
0
5
Order By: Relevance
“…The phases of analysis and synthesis, in turn, promote reflection, which is crucial in learning because it modifies behaviors due to the acquired knowledge and interpretation of the experienced situations (43) . Studies have identified that nursing students who participate in structured debriefing and synthesize all the components of a simulated experience in a context they consider meaningful (2,26) find it easier to reflect assertively and comprehensively (24) , develop critical thinking and the ability to integrate new information and improve their clinical judgment ability (26) . Today, the body of evidence that evaluates debriefing methods is increasing although a given method is usually chosen according to the personal preference of the facilitator without regard for the context and the objectives (4) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The phases of analysis and synthesis, in turn, promote reflection, which is crucial in learning because it modifies behaviors due to the acquired knowledge and interpretation of the experienced situations (43) . Studies have identified that nursing students who participate in structured debriefing and synthesize all the components of a simulated experience in a context they consider meaningful (2,26) find it easier to reflect assertively and comprehensively (24) , develop critical thinking and the ability to integrate new information and improve their clinical judgment ability (26) . Today, the body of evidence that evaluates debriefing methods is increasing although a given method is usually chosen according to the personal preference of the facilitator without regard for the context and the objectives (4) .…”
Section: Discussionmentioning
confidence: 99%
“…The increasing complexity of health systems and greater awareness of user rights have forced nurses to adapt to this scenario (1) . Simulation in initial and continuing nursing education to support teaching and learning is currently considered one of the best ways to improve the capacity to reflect and reason clinically and develop competencies (2) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher the dispositional resilience level, the lower the burnout situations in nurses who can successfully overcome obstacles, uncertainties, and adverse conditions [ 43 ]. Simulation workshops have been indicated as an effective strategy to improve self-efficacy and resilience [ 44 ]. We suggest that nurses can provide a better quality of care in nursing practice by these training programs.…”
Section: Discussionmentioning
confidence: 99%
“…As new teaching strategies are being introduced in India, it is vital to ascertain the teacher self-efficacy of the Indian nursing faculty. According to Britton, K. L., [14] higher self-efficacy is achieved by understanding and experience which affect teaching behaviors and professional progress and is integral to increasing self-efficacy [15].…”
Section: Introductionmentioning
confidence: 99%